Benefits and Drawbacks of Operational Objetives in Educational or Social Programs: An Example in Educational Psychology. - López Ulloa, Susana (Revista de Psicología, 2004)
This research studied the outcome of the variable: “level of specificity in writing educational objectives”. The analysis of the results compiled by three interviews applied to 51 teachers revealed correlation coefficients that, even though moderate, were statistically significant and showed that the teachers tend to write more specific educational objectives the lower the age of the students, the grade, and the number of students in the class. In addition, the level of specificity of the educational objectives cumwritten by the teachers has a positive and statistically significant correlation to a successful experience in applying behavioral techniques for classroom management. Finally, neither the number of courses in which the teacher studied operant conditioning, nor the usefulness assigned to these techniques showed a statistically significant correlation with the level of specificity of the reported objectives. The study discusses the relationship between general and specific goals.